FINANCIAL PERFORMANCE DETERMINANT AND ITS IMPACT ON REGIONAL ECONOMIC GROWTH OF TABALONG DISTRICT - Maryani, Dedeh; Indrayani, Etin; Zulaika, Siti; Maemunah, Cucu (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2025)
The purpose of this research is to explanation of regional revenue and capital expenditure on regional financial performance and its impact on economic growth. A quantitative method with hypothesis testing through path analysis was employed. The research investigates four variables: regional revenue and capital expenditure as independent variables, regional financial performance as the intervening variable, and economic growth as the dependent variable. The sample comprises complete data over a ten-year period (2012–2023). The findings indicate that regional revenue and capital expenditure significantly influence regional financial performance, accounting for 74.30% of the variance, while regional financial performance strongly affects economic growth, contributing 81.00%. This study proposes a novel conceptual framework that integrates the dynamic interrelationships among these variables. It advances previous research by highlighting the collective and interdependent effects of fiscal factors on regional development, offering new theoretical insights and practical implications for regional policy and financial management. Keywords : Regional income, capital expenditure, regional financial performance , economic growth, new concept.